A cricket game, a train ticket and a vacuum to be filled: Ayer's logical positivism as a focal point for post-war British cultural struggles. Issue 6 (1st November 2020) - Tuboly, Adam Tamas
ABSTRACT: In 1948, A.J. Ayer was attacked on the pages of The New Statesman and Nation magazine where it was claimed that his views were partly responsible for increasingly Fascist attitudes at Oxford. Ayer was charged with promoting a philosophy of values (or one lacking therein) that allowed Fascism to fill the moral vacuum. Ayer noted that he knew who had written the article (and the ones that followed) and that this person had done so for entirely contingent and non-philosophical reasons. This paper aims to examine the historical context by discussing the article and the events that followed it; to show that the specific charges against Ayer were rooted in deeper philosophical/practical issues, namely the nature and status of philosophy; and to demonstrate that logical empiricism, or rather logical positivism as a movement, was indeed especially sensitive to political issues.